Effect of waveform of ac voltage on the morphology and crystallinity of electrochemically assembled platinum nanowires - Nerowski, Alexander; Poetschke, Markus; Wiesenhuetter, Ulrich; Nicolai, Juergen; Cikalova, Ulana; Dianat, Arezoo; Erbe, Artur; Opitz, Joerg; Bobeth, Manfred; Baraban, Larysa; Cuniberti, Gianaurelio (Giovanni) (Langmuir, 2014)
Here we present electrochemically grown ultrathin platinum nanowires and demonstrate that their morphology and crystalline structure can be tuned by the waveform of the alternating voltage applied to the microelectrodes. The structure of the nanowires was analyzed by scanning and transmission electron microscopy. The voltage signal, applied to grow the nanowires, consisted of several Fourier components of a square-shaped wave. We observed that, depending on the number of Fourier components, the morphology of the nanowires changed from branched dendritic-like patterns to straight wires and the wire crystallinity changed from polycrystalline to highly oriented growth with the [111] direction of platinum crystallites along the nanowire axis. We propose a simple model to explain this intriguing observation. © 2014 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20